2016
DOI: 10.1002/2015gc006206
|View full text |Cite
|
Sign up to set email alerts
|

Shear velocity structure beneath the central United States: implications for the origin of the Illinois Basin and intraplate seismicity

Abstract: We present new estimates of lithospheric shear velocities for the intraplate seismic zones and the Illinois Basin in the U.S. midcontinent by analyzing teleseismic Rayleigh waves. We find that relatively high crustal shear velocities (VS) characterize the southern Illinois Basin, while relatively low crustal velocities characterize the middle and lower crust of the central and northern Illinois Basin. The observed high crustal velocities may correspond to high‐density mafic intrusions emplaced into the crust d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
61
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(102 citation statements)
references
References 120 publications
28
61
8
Order By: Relevance
“…In the region of the Reelfoot Rift, Mooney et al [] and Nelson and Zhang [] observed high‐velocity lower crust in seismic refraction profiles that they interpreted as a “rift pillow” created by magmatic differentiation during the rifting event. Liang and Langston [] and Chen et al [] confirmed the presence of high‐velocity lower crust using tomographic techniques. The result from our study and some other recent studies [ McGlannan and Gilbert , ; Shen and Ritzwoller , ] all show a relatively thin crust beneath the Reelfoot Rift and the Rough Creek Graben.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…In the region of the Reelfoot Rift, Mooney et al [] and Nelson and Zhang [] observed high‐velocity lower crust in seismic refraction profiles that they interpreted as a “rift pillow” created by magmatic differentiation during the rifting event. Liang and Langston [] and Chen et al [] confirmed the presence of high‐velocity lower crust using tomographic techniques. The result from our study and some other recent studies [ McGlannan and Gilbert , ; Shen and Ritzwoller , ] all show a relatively thin crust beneath the Reelfoot Rift and the Rough Creek Graben.…”
Section: Discussionmentioning
confidence: 68%
“…The St. Louis Arm, defined by Braile et al [, , ] as a rift extension following the strike of the Mississippi River between Missouri and Illinois, is coincident with the large Moho offset (5–10 km) discussed in section 5.2. Although similar velocity patterns are observed among these three arms in the lower crust and upper mantle [ Chen et al ., ; Savage et al ., ], our results on the spatial distribution of crustal velocity discontinuities contradict the concept of the St. Louis and Indiana Arms. Specifically, both the localized, shallow Moho (Figure ) and the confined, thin crystalline crust (Figure ) suggest that rifting of the crust directly impacted only the areas of the Reelfoot Rift and Rough Creek Graben.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Equalizing the rank on the finer grid increases the variance of the model parameters at long periods more than on the coarse grid, and we found that on the 0.8° grid, we were unable to usefully equalize the rank at 143 s, the longest period, so we dropped that period altogether in the second step. Rau and Forsyth [] and Chen et al [] used multiple steps, but we found that further refinement of the grid was of marginal value, given the noise level and scattering in the waveforms in this experiment.…”
Section: Methodsmentioning
confidence: 99%